A Study on the Role of Media in Changing Society’s Perception of LGBT Community - Biju, Brinda S; K, Sreena (International Journal of Psychosocial Rehabilitation, 2020)
LGBT Community belongs to one of the most vulnerable and marginalized populations in India, specifically in Kerala. But recently there is a notable shift in the inclusion of LGBT in Kerala. In India, Kerala is the first state to set up a welfare agreement for the transgender community in 2015. The state department of social justice had issued the policy to uphold the constitutional rights of transgender, taking into account the Supreme Court judgment (2014).On 2018 September 6, a five-member bench of the Indian penal code (IPC), decriminalized the British-era Section377 of the Indian Penal Code. It is an extremely significant victory for the LGBT community. The Queer political activism in Kerala developed much before this and has gained critical grounds. This paper locates how the media has contributed to this major change. This study uses a mixed-method approach by analyzing both the qualitative and quantitative analysis of the data. It shows that the media can play a transitional role in shaping political attitudes towards sexuality and minorities in general.